2009
DOI: 10.1007/s11430-009-0039-6
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of the close-off depth and the stable isotopic records along a 109.91 m ice core from Dome A, Antarctica

Abstract: Citation: Hou S G, Li Y S, Xiao C D, et al. Preliminary results of the close-off depth and the stable isotopic records along a 109.91 m ice core from Dome A, Antarctica. A 109.91 m ice core was recovered from Dome A (or Dome Argus), the highest ice feature in Antarctica, during the 2004/05 austral summer by the 21st Chinese National Antarctic Research Expedition (CHINARE-21). Both methane profile along the core and firn densification model calculation suggest that the close-off depth is at about 102.0 m with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Depth-year series were calculated based on the settled marked layers and the density of each sample. The calculated average snow accumulation rate was 18.2 kg m -2 a -1 from 1965 to 1993 and 22.4 kg m -2 a -1 from 1993 to 2009, respectively, which was consistent with former observations in Dome A [ 2 , 26 ]. Our dating results was supported by previous studies [ 2 , 26 , 27 ].…”
Section: Methodssupporting
confidence: 90%
“…Depth-year series were calculated based on the settled marked layers and the density of each sample. The calculated average snow accumulation rate was 18.2 kg m -2 a -1 from 1965 to 1993 and 22.4 kg m -2 a -1 from 1993 to 2009, respectively, which was consistent with former observations in Dome A [ 2 , 26 ]. Our dating results was supported by previous studies [ 2 , 26 , 27 ].…”
Section: Methodssupporting
confidence: 90%
“…3a), whereas no significant changes have been apparent at Dome A (Fig. 1) since 1260 (Ding et al, 2011a;Hou et al, 2009; (β40) and Tambora-1960s (β150) with respect to the SMB values of the entire ice core length (βtot); sites with SMBs greater than 300 kg m −2 yr −1 and lower than 300 kg m −2 yr −1 are represented with triangles and filled circles, respectively. Larger symbols indicate sites included in the verified ( ) dataset.…”
Section: Resultsmentioning
confidence: 99%
“…No significant trend was found in accumulation rates in cores up to 100 years old before 1996 from Amundsenisen in DML . The Dome C area (Frezzotti et al, 2005;Urbini et al, 2008) has exhibited high accumulation since the 1960s, as observed along the traverse between Dome Fuji and EPICA DML, whereas no significant changes have been apparent at Dome A since 1260 (Ding et al, 2011;Hou et al, 2009). In the Talos Dome area at the border between EAP and VL, century-scale variability shows a slight increase (of a few percent) in accumulation rates over the last 200 years, in particular since the 1960s, compared with the period 1816-1965 (Frezzotti et al, 2007).…”
Section: Drivers Of Regional Precipitation 321 East Antarctic Platementioning
confidence: 89%